Electrochemical processes and systems: application for tutors - Ved, M. V.; Volobuyev, M. M.; Stepanova, I. I.; Yermolenko, I. Yu.; Karakurkchi, A. V. (Національний технічний університет "Харківський політехнічний інститут", 2018)
The features of redox reactions and the principles of their balancing according to the medium composition are considered. The basic representations about electrochemical processes and systems are outlined. The reactions and principles of chemical sources of electric energy and electrolysis systems functioning are analyzed. A general idea is given about the chemical properties of metals, corrosion resistance in environments of various aggressiveness, and the protection principles are given. Multivariate tasks and exercises for students, and PhD student’s classroom and independent work are offered. For teachers, PhD students and students of universities of specialties "Chemical technologies and engineering", "Biotechnologies and bioengineering", "Oil and gas engineering and technologies".

Розглянуто особливості окисно-відновних реакцій і принципи їх балансування залежно від складу середовища. Викладено фундаментальні уявлення про електрохімічні процеси і системи. Проаналізовано перебіг реакцій і принципи функціонування хімічних джерел електричної енергії та систем електролізу. Узагальнено уявлення щодо хімічних властивостей металів, корозійної стійкості у середовищах різної агресивності та наведено принципи організації захисту від руйнування. Запропоновано багатоваріантні завдання та вправи для аудиторної та самостійної роботи студентів і аспірантів. Розраховано на викладачів, аспірантів і студентів вищих навчальних закладів спеціальностей "Хімічні технології та інженерія”, "Біотехнології та біоінженерія", "Нафтогазова інженерія та технології".
Keywords: oxidation-reduction reactions; electrochemical energy storage; conversion; electrolytic cells; transition metals; chemical properties of metals; corrosion; corrosion protection; alloying of metals; alteration of environment; protective coatings; corrosion inhibitors; electrochemical protection